A Modified Critical Nitrogen Dilution Curve for Winter Wheat to Diagnose Nitrogen Status Under Different Nitrogen and Irrigation Rates - Zhao, Yu; Chen, Pengfei; Li, Zhenhai; Casa, Raffaele; Feng, Haikuan; Yang, Guijun; Yang, Wude; Wang, Jianwen; Xu, Xiaobin (Frontiers in Plant Science, 2020)
The accuracy of nitrogen diagnosis is vital to improve nitrogen utilization efficiency. The standard critical nitrogen concentration (standard Nc) dilution curves, an expression of the allometric scaling, exists widely in nature and are used to diagnose the nitrogen status of crops. Currently, lots of standard Nc dilution curves were constructed and validated for several crops based on different nitrogen (N) fertilizer treatments, however standard Nc dilution curves are changed as the irrigation management changing. To construct a N diagnostic model under the coupling effect of irrigation and fertilizer managements, this paper not only constructed the standard Nc dilution curves under different irrigation rates, but also introduced plant water content (PWC), leaf water content (LWC), leaf area index (LAI), equivalent water thickness (EWT) and leaf area duration (LAD) to construct a modified Nc (mNc) dilution curve. The mNc dilution curves were designed based on aboveground dry biomass (AGB) as the first layer information and the second layer information of different agronomy parameters (PWC, LWC, LAI, EWT and LAD), using the principle of hierarchical linear model (HLM). The results showed that: (1) The parameter “a” and “b” of standard Nc dilution curves ranged from 5.17 to 6.52 and -0.69 to -0.38. Parameter “b” is easily affected by different management conditions. (2) The performance of standard Nc dilution models obtained by cross validation method was worse than that of mNc dilution models. The Nc dilution curve based on 4 years was described by the negative power equation Nc=5.05*AGB-0.47, with R2 and nRMSE of 0.63 and 0.21, respectively; (2) the mNc dilution curve considers different treatments and was represented by the equation mNc = aAGB-b, where a = 2.09*PWC+3.24, b =-0.02*LAI+0.51, with R2 and nRMSE of 0.79 and 0.13, respectively. There would be some problems in using standard Nc dilution methods to guide field management, however this study provides a reliable method for constructing mNc dilution curves under different water and N fertilizer management.